2022
DOI: 10.3390/v14030455
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Circulating Levels of SARS-CoV-2 Antibodies and Inflammatory Mediators in Healthcare Workers and COVID-19 Patients

Abstract: Advances in knowledge of the pathophysiology of COVID-19 have been acquired; however, the host factors that could explain the mild and severe forms of the disease are not fully understood. Thus, we proposed to evaluate anti-SARS-CoV-2 antibodies and the inflammatory response of different groups of individuals, including healthcare workers (HCW), sick and dead COVID-19 patients and also recovered patients to contribute to this knowledge gap. Our objective is to relate the clinical evolution of these individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
4
1
Order By: Relevance
“…The ability of the AZD1222 vaccine to induce neutralizing antibody production after vaccination was demonstrated [35]. Although here, we did not show neutralizing antibody data in this study, a previous study from our group noted a positive correlation between IgG antibodies detected by the commercial ELISA kit and neutralizing antibody titers measured by the plaque reduction neutralization test (PRNT), indicating that most antibodies detectable in patients by this kit are neutralizing [17]. Therefore, if we consider the bene ts of BAFF in developing the humoral response during infection, it could be interesting for COVID-19 vaccines to incorporate BAFF molecular adjuvants to increase protection by inducing a better humoral response.…”
Section: Study Approvalcontrasting
confidence: 47%
See 1 more Smart Citation
“…The ability of the AZD1222 vaccine to induce neutralizing antibody production after vaccination was demonstrated [35]. Although here, we did not show neutralizing antibody data in this study, a previous study from our group noted a positive correlation between IgG antibodies detected by the commercial ELISA kit and neutralizing antibody titers measured by the plaque reduction neutralization test (PRNT), indicating that most antibodies detectable in patients by this kit are neutralizing [17]. Therefore, if we consider the bene ts of BAFF in developing the humoral response during infection, it could be interesting for COVID-19 vaccines to incorporate BAFF molecular adjuvants to increase protection by inducing a better humoral response.…”
Section: Study Approvalcontrasting
confidence: 47%
“…A cross-sectional study was conducted in patients infected by SARS-CoV-2 and healthy individuals vaccinated with AZD1222 (ChAdOx nCoV-19, AstraZeneca) (Table 1). Two groups of COVID-19 patients were chosen: acute patients with COVID-19 were treated at Hospital Rede-Casa, Rio de Janeiro, Brazil, between March and June 2020 [17], and the recovered group comprised patients who no longer presented clinical symptoms [18]. The 11 vaccine recipients received the ChAdOx1 nCoV-19 vaccine (AZD1222).…”
Section: Study Design and Blood Sample Collectionmentioning
confidence: 99%
“…In a longer duration of SARS-CoV-2 infection, from 14 days to four weeks, CCL-2 levels were reported to be similar between severe and mild infection ( Xu et al, 2020 ; Zhao et al, 2020 ). De-Oliviera-Pinto et al reported no significant difference in CCL-2 levels between symptomatic and asymptomatic SARS-CoV-2 infected individuals, and also those who recovered ( De-Oliveira-Pinto et al, 2022 ). Similar to the findings, we found that the CCL-2 levels of mild-to-moderately SARS-CoV-2 infected pre-vaccinated individuals were significantly different compared to healthy, unexposed controls, but not with individuals recovered.…”
Section: Discussionmentioning
confidence: 99%
“…We found a higher frequency of IL-10 + Treg in unstimulated or Pool CoV-2-stimulated Mild Recovered PBMC compared to that in HC and Severe Recovered groups, strengthening the hypothesis of persistent immune changes after the resolution of infection ( 27 , 28 ). Although some studies correlate cytokines such as IL-6 and IL-10 as predictors of COVID-19 severity, elevated IL-10 levels could act to moderate excessive inflammation even though it is not able to do so ( 29 31 ).…”
Section: Discussionmentioning
confidence: 99%